Assessing the relationship between food security, the child support grant and child care arrangements - Tyabashe, Babalwa (University of the Western Cape, 2020)
Magister Artium (Social Work) - MA(SW) === Food insecurity exists when people lack access to sufficient quantities of safe and nutritious food which encourages normal growth and development. Given South Africa’s high poverty and unemployment levels, food insecurity has become endemic in many communities. The purpose of the study was to determine and explore the relationship between food insecurity, child care arrangements and the child support grant (CSG). The study was conducted among a sample of 120 participants, comprising both CSG recipients and non-recipients (who were purposefully selected from an ongoing cohort study), residing in Langa township in Cape Town. A sequential, mixed-model research design was used, in which both qualitative and quantitative research methods were applied. Data was collected by means of questionnaires, interviews and focus groups. The results were analysed using SPSS and Atlas ti software. The ecological systems theory being used as a theoretical framework to explore the different dimensions of child care arrangements. In the literature it is hypothesised that food insecure families are more likely to have child care arrangement instabilities. Interestingly, the study’s findings did not support this hypothesis. Although most of the participants were unemployed, they generally stayed at home to care for their children because they were recipients of the CSG. Therefore, despite being food insecure, many households had stable child care arrangements because of the CSG. Child support grant recipient households experienced hunger less acutely than households that did not receive the grant. Of course, social protection mechanisms, like grants, do not represent a sustainable solution to South Africa’s unemployment and food insecurity challenges. The researcher therefore provides a number of recommendations on how government and civil society can ameliorate the plight of poor households.